Menanamkan Nilai Kewirausahaan Melalui Kegiatan Market Day - Leonita Siwiyanti Suharyoto (Pusat Penerbitan Universitas (P2U) Unisba, 2017)
Abstract Entrepreneurship is an attitude of mental and spirit which is always active and creative, down to earth, and striving in order to increase profit for business activities. There are six basic values of entrepreneurship which can be integrated in early childhood learning process, namely: independent, creative, risk taker, leadership, action orientation, and hard work. The embedding of entrepreneur's character was one of the ways in realizing the vision of Sabilina Islamic Kindergarten by making the program